Effect of the Localized Insecticides Spray Technique to Control Halyomorpha halys in Actinidia chinensis Orchards - Landi, Matteo; Preti, Michele; Masetti, Antonio; Spinelli, Francesco (Insects (Basel, Switzerland), 2024)
Kiwifruit (Actinidia chinensis) cultivation is expanding worldwide, with China, New Zealand, and Italy being the major producing countries. Halyomorpha halys, the brown marmorated stink bug, is raising serious concerns to kiwifruit cultivation both in China and Italy. This study aimed at improving the chemical control efficacy against this pest by comparing two insecticide spray techniques (a conventional ray atomizer and a trumpet-modified atomizer adapted for localized spray application) in kiwifruit. In fact, kiwifruit is often grown with a ‘pergola’ training system, which may reduce the effectiveness of insecticide penetration into the canopy. Experiments were performed in naturally infested orchards of both Actinidia chinensis var. chinensis ‘Jintao’ and A. chinensis var. deliciosa ‘Hayward’. Furthermore, mesh cages containing H. halys adults were deployed within orchards to assess the insects’ mortality at 1, 3, 7, and 10 days after an insecticide application with two spray techniques during two consecutive seasons. In the cultivar ‘Jintao’, the two systems performed similarly, while in the cultivar ‘Hayward’, an overall significantly higher insect mortality was recorded with the trumpet atomizer (94–100%) compared to the conventional atomizer (59–78%). Crop damage was also evaluated on both cultivars, simulating the grower insecticide applications with the two spray techniques. At harvest, no difference emerged between the spray techniques, which provided a significantly better protection compared to the untreated control (12–17% compared to 33–47% of injured fruits). Further investigations in this direction are needed also considering the restriction of insecticidal active substances ongoing in the European Union and the need to maximize the efficacy of the available tools.